ENFSI Firearms/GSR Working Group Meeting (Espoo, Finland) - A. S. Likhachev (Теория и практика судебной экспертизы)
The paper reports on the outcomes of the 24th Annual Meeting of the Firearms/GSR Expert Working Group of the European Network of Forensic Science Institutes (ENFSI) that was held in October 2017 in Finland.